Hubungan Tingkat Pengetahuan Dengan Manajemen Diri dan Kepatuhan Penggunaan Obat Pasien Dabetes Mellitus di Klinik Gading Yogyakarta - Yoga Dwi Saputra; Nur Aini Widiastuti (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Diabetes mellitus is a global disease. This study aimed to determine the relationship between the level of knowledge and accuracy of diabetes mellitus drug use and the relationship between the level of knowledge and adherence to diabetes mellitus drug use at the Gading Clinic Yogyakarta. This study was observational. Participants were typed 2 diabetes mellitus patients in the JKN referral program at the Gading Yogyakarta Clinic. Data were collected through questionnaires on knowledge related to diabetes mellitus, accuracy, and adherence. Data analysis was performed using the SPSS program with the chisquare test. The results showed a correlation between knowledge and self-management (p = 0.007), while no correlation was found between knowledge and medication adherence (p = 0.734). Based on these results, there was a correlation between diabetes mellitus knowledge and self-management in patients with type 2 diabetes mellitus at the Gading Clinic in Yogyakarta.